The Use of the Book Al-Muyassar Fī ‘Ilmin Nahwi in Nahwu Learning at Ma’had Al-Jāmi‘ah IAIN Ternate - Yuliana Bugis; Andi Nurmawaddah; Muhammad Ridha Assagaf (Golden Ratio of Social Science and Education, 2026)
Learning nahwu is a fundamental component of mastering Arabic, especially in understanding classical Islamic texts. However, nahwu material is often perceived as difficult by students because of its abstract and theoretical presentation. This study aims to describe the use of Al-Muyassar Fī ‘Ilmin Nahwi in learning nahwu at Ma’had Al-Jāmi‘ah IAIN Ternate and analyze its advantages and limitations. This study employed a descriptive qualitative approach. Data collection techniques included learning observations, interviews with musyrif and students, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that Al-Muyassar Fī ‘Ilmin Nahwi is the main book because of its systematic, concise, and easy-to-understand presentation for beginner students. The use of this book can improve basic nahwu understanding and student learning motivation in the following ways. The obstacles found include limited learning time and variations in students' Arabic language backgrounds. This study recommends strengthening contextual methods and intensive mentoring for optimal use of the book.